Thyroid Hormones and Cancer: A Comprehensive Review of Preclinical and Clinical Studies - Krashin, Eilon; Piekiełko-Witkowska, Agnieszka; Ellis, Martin; Ashur-Fabian, Osnat (Frontiers in Endocrinology, 2019)
Thyroid hormones play a key role in normal growth, development and metabolism. Over a century of research has supported a putative relationship between thyroid hormones and the biology of various cancer types. In vitro studies as well as research in animal models demonstrated an effect of the thyroid hormones T3 and T4 on cancer proliferation, apoptosis, invasiveness and angiogenesis. Thyroid hormones mediate their effects on the cancer cell through several nongenomic pathways including activation of the plasma membrane receptor integrin αvβ3. Furthermore, cancer development and progression is also affected by dysregulation of local bioavailability of thyroid hormones. Case-control and population-based studies provide conflicting results regarding the association between thyroid hormones and cancer. However a large body of evidence suggests that subclinical and clinical hyperthyroidism increase the risk of several solid malignancies while hypothyroidism may delay onset or reduce aggressiveness of cancer. Additional support is provided from studies in which dysregulation of the thyroid hormone axis secondary to cancer treatment or thyroid hormone supplementation was shown to affect cancer outcomes. Recent preclinical and clinical studies in various cancer types have further shown promising outcomes following chemical reduction of thyroid hormones or inhibition or their binding to the integrin receptor. This review provides a comprehensive overview of the preclinical and clinical research conducted so far